Sócrates por Xenofonte: a filosofia em ação para a construção de um homem integralmente forte e senhor de si mesmo (Nuntius Antiquus, 2008)
Xenophon’s Socrates, by making a distinction between things that are under our control and things that are not, decides that thought should occupies itself only with human things, in order that the individual can achieve a degree of freedom that allows him to be a good friend, an exemplar warrior and politician, so that his soul can become good, beautiful and noble through self-knowledge.